Kesantrian Management: Strategy and Efficiency of Santri’s Learning Activities (A Case Study at Pondok Pesantren Babussalam Cimanggis Depok) - Suharyat, Yayat; Nurhayati, Sri; Rohmat, Rohmat; Mista, Hunaidah; Hidayat, Ahmad Wahyu; Adeoye, Moses Adeleke (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2023)
This study aims to explore and analyze the management of Santri (students who study in Islamic boarding schools) in increasing the efficiency of Santri learning activities. This study used a qualitative approach with a descriptive method. Data were collected through interviews, observation, and document review. The research subjects were the students and teachers/ustadz who were included in the management of the Santri and the Babussalam Islamic Boarding School, Cimanggis, Depok, as the research site. The study found that various obstacles faced by Santri to increase the efficiency of Santri’s learning activities require good management of Santri and strategies so that Islamic boarding schools can achieve the goals. The learning management and strategy of the Santri are the success factors in producing superior Santri as the Rabbani generation, the successor of the Prophets’ treatises.